Service Quality and Student Satisfaction in High School Registrar Operations - Infornon, Maria Beylen I.; Almaden, Antoniette M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the relationship between registrar general services, physical setup, and staff familiarity in shaping student satisfaction in a high school setting. Using a quantitative descriptive-correlational design, responses from 264 students were analyzed through mean scores and Pearson’s correlation coefficients. Physical setup received the highest mean score (3.35), followed by staff familiarity (3.09) and general services (2.91). Significant positive correlations were found between general services and physical setup (r = 0.56), general services and staff familiarity (r = 0.34), and physical setup and staff familiarity (r = 0.41). Based on these results, the study recommends infrastructure improvements, empathy-based staff training, and digital service enhancements to foster a more student-centered registrar experience.